Chitosan‐based gel film electrolytes containing ionic liquid and lithium salt for energy storage applications. Issue 26 (16th March 2015) - Chupp, Jeremy; Shellikeri, Annadanesh; Palui, Goutam; Chatterjee, Jhunu
ABSTRACT Fabrication, characterization, and a comparative study have been performed for chitosan‐based polymer electrolytes using two different dispersion media. Chitosan gel film (solid) electrolytes are fabricated using acetic acid or adipic acid as the dispersant for chitosan in combination with ionic liquid and lithium salt. This quaternary system of chitosan, acetic acid or adipic acid, 1‐butyl‐3‐methylimadazolium tetrafluoroborate (ionic liquid), and lithium chloride is formed as an electrolyte for potential secondary energy storage applications. The ionic conductivities, thermal, structural, and morphological properties for these electrolytes are compared. The ionic conductivities for chitosan/adipic acid (CHAD) and for chitosan/acetic acid (CHAC) systems are in the range of 3.71 × 10−4−4.6 × 10−3 and 1.3 × 10−4 −3.2 × 10−3 S cm−1, respectively. The thermal stability of CHAD‐based electrolytes is determined to be higher than that of CHAC‐based electrolytes. Preliminary studies are performed to determine the electrochemical stability of these materials as solid film electrolytes for electrochemical supercapacitors. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42143.